Corrosion Resistance and Cytocompatibility of Magnesium-Calcium Alloys Modified with Zinc- or Gallium-Doped Calcium Phosphate Coatings; ACS Applied Materials and Interfaces; Vol. 14, iss. 1 - Tamay D. G. Dilara Goksu; Gokyer S. Seyda; Schmidt J. Jurgen; Vladesku A. Alina; Huri P. Y. Pinar Yilgor; Hasirci V. Vasif; Hasirci N. Nesrin (2022, 2022)
Title screen